Felix Nørgaard, Else Roesdahl, Roar Skovmand (red.): Aggersborg gennem 1000 år fra vikingeborg til slægtsgaard. (Poul Kristensens Forlag, Herning 1986). 233 s., 260 kr. - Linton, Michael (Historie/Jyske Samlinger, 1989)
-